Assessment of Wetland Ecosystem Services in Tien Yen Estuary, Quang Ninh Province - Thi Dieu Linh, Nguyen; Kinh Bac, Dang; Thi Phuong, Vu; Quang Hai, Truong; Thi Thu Huong, Hoang (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 4DO - 10.25073/2588-1094/vnuees.4811, 2021)
Wetland ecosystems have provided high biological productivity, played an important role in the stability and development of coastal people. The wetland ecosystem service (WES) assessment is an effective tool for calculating direct and indirect benefits that humans obtained from these ecosystems based on monetary valuation. The value of WES in the Tien Yen estuary area has been assessed and calculated using a combination of different methods, including cost-benefit analysis, questionnaire survey, and remote sensing and GIS. The results showed the particular monetary values of 11 WES obtained from 10 wetland ecosystems and total WES value in the study area. The outcome can become the scientific basis to choose the suitable solutions for sustainable use of natural resources in the relationship between preservation and exploitation of wetlands in the future.